Implementasi Program Pelayanan Tanah Akhir Pekan (PELATARAN): Peningkatan Kualitas Pelayanan Publik di Kantor ATR/BPN Kabupaten Serang Berdasarkan UU Nomor 25 Tahun 2009 - Fadhila Fauzia Syarif; H. E. Rakhmat Jazuli; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of the Weekend Land Service Program (PELATARAN) at the ATR/BPN Office of Serang Regency as an instrument for improving public service quality under Law Number 25 of 2009 on Public Services. Employing an empirical juridical method with descriptive-analytical specification, the research integrates primary data obtained from interviews and field observations with secondary legal materials, including statutory regulations and internal administrative instruments governing the program. The findings demonstrate that PELATARAN possesses a legally defensible foundation within the framework of governmental administrative authority, particularly through the alignment between institutional mandates in land administration and the operational legitimacy provided by ministerial circulars and local decrees. Empirically, the program enhances accessibility and procedural certainty by expanding service availability beyond conventional working days, yet its effectiveness remains contingent upon human resource capacity, consistency of standard implementation, and the institutionalization of measurable service indicators. The study further highlights that accountability mechanisms, complaint handling systems, and maladministration prevention are decisive determinants of sustainable service quality. The research contributes by linking normative legality with empirical governance performance in land service innovation.